Gender dynamics in climate information services: a systematic review of intersectional influences and strategies for smallholder farmers in Sub-Saharan Africa - Khatibu, Salma; Kissoka, Gasper (Frontiers in Climate, 2025)
IntroductionThe adoption of Climate Information Services (CIS) in Sub-Saharan Africa (SSA) is critical for enhancing agricultural resilience amid escalating climate variability, yet equitable access remains hindered by systemic gender disparities and insufficient attention to intersectional factors. This review examines the dynamics in gender-responsive CIS adoption and use, emphasizing the neglect of intersecting social dimensions, which exacerbate barriers for marginalized women.MethodologyA systematic review of peer-reviewed literature was conducted, focusing on studies addressing CIS adoption in SSA from 2014 to 2024. Sources were drawn from databases such as Web of Science, Scopus, PubMed, CABI Abstracts, and Africa Portal. Qualitative and quantitative studies were analyzed to assess methodological approaches.Key findingsAlthough gender is widely addressed in the reviewed literature, only 4 of the 19 studies (21%) explicitly analyzed more than one intersecting identity category. This demonstrates a substantial gap in intersectional evidence within CIS research, limiting understanding of compounded barriers faced by women who are constrained by asset scarcity and social exclusion. Resource barriers, such as limited access to mobile phones and radios, are acknowledged, but cost-effectiveness evidence of interventions like subsidized technologies are scarce. The lack of gender-disaggregated data hinders tailored CIS design.RecommendationsFuture research should prioritize in-depth, qualitative studies to explore how intersecting identities shape CIS access, employing participatory methods to capture cultural and social dynamics. These strategies aim to bridge gender gaps, enhance climate resilience, formulate gender inclusive policies and foster sustainable agricultural development in Sub-Saharan Africa.